The Era of Interactive Media - Jin, Jesse S.; Xu, Changsheng; Xu, Min.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
none
Best Papers and Runner-ups -- Face Detection, Recognition and Synthesis -- Video Coding and Transmission -- Audio, image and video quality assessment -- Audio and image classification -- Stereo Image and Video Analysis -- Object Detection -- Action Recognition and Surveillance -- Visual Analysis and Retrieval -- Watermarking and Image Processing -- Applications.
Keywords: Computer science; Computer network architectures; Computer Communication Networks; Information systems; Multimedia systems; Computer Science; Multimedia Information Systems; Computer Communication Networks; Information Systems Applications (incl. Internet).; Computer Systems Organization and Communication Networks; Information Systems and Communication Service